Increasing role of arthropod bites in tularaemia transmission in Poland – case reports and diagnostic methods - Kamila Formińska; Aleksandra A Zasada; Waldemar Rastawicki; Karolina Śmietańska; Dorota Bander; Marta Wawrzynowicz-Syczewska; Mariya Yanushevych; Jolanta Niścigórska-Olsen; Marek Wawszczak (Annals of Agricultural and Environmental Medicine, 2015)
The study describes four cases of tularaemia – one developed after contact with rabbits and three developed after an arthropod bite. Due to non-specific clinical symptoms, accurate diagnosis of tularaemia may be difficult. The increasing contribution of the arthropod vectors in the transmission of the disease indicates that special effort should be made to apply sensitive and specific diagnostic methods for tularaemia, and to remind health-care workers about this route of [i]Francisella tularensis[/i] infections. The advantages and disadvantages of various diagnostic methods – molecular, serological and microbiological culture – are discussed. The PCR as a rapid and proper diagnostic method for ulceroglandular tularaemia is presented.